OPTIMALISASI PERSEDIAAN BAHAN BAKU BAGI KELANCARAN PROSES PRODUKSI PADA TOKO ROTI DWI JAYA BAKERY KUPANG - Yohanes M M Taek Bete; Ni Putu Nursiani; Wehelmina M Ndoen (Universitas Nusa Cendana, 2020)
This research will focus on the controlling of raw materials supply to expedite the production process.This study aims to determine and analyze the optimization of raw material supplies in the Dwi JayaBakery Kupang. The method used in this study is the EOQ (economic order quantity), Safety Stock,Re-order Point methods. The instruments used in this study were interviews, literature studies, anddocumentation. The results showed that, in ordering raw materials, Dwi Jaya Bakery still usesconventional calculations where by predicting the amount of raw materials replenishment if there isonly a small amount of supplies, and also has not applied safety stock and ROP optimally, so thatsometimes raw materials in the warehouse were lack of inventory, it indirectly affect profits from DwiJaya Bakery and which results in delays in ordering so that it can disrupt the production process. Keywords: Optimization of Raw Material Inventory, Production Process, EOQ (Economic OrderQuantity